Helicoidal peripapillary chorioretinal degeneration: electrophysiology and psychophysics in 17 patients. Issue 3 (1st March 1998) - Eysteinsson, Thor; Jónasson, Fridbert; Jónsson, Vésteinn; Bird, Alan C
Abstract : AIMS: To characterise retinal function using electrophysiological and psychophysical tests in 17 patients with helicoidal peripapillary chorioretinal degeneration. METHODS: The electroretinogram (ERG) was recorded using gold foil corneal electrodes. The electro-oculogram (EOG) was recorded using a standard protocol. Dark adaptometry was recorded with an SST-1 dark adaptometer and colour vision assessed with Ishihara plates and Farnsworth D-15. RESULTS: All subjects had a recordable ERG. The amplitudes and implicit times of the a- and b-waves were within normal limits at all luminances in five subjects (age 21–70 years, mean 40 years). The ERG of six (age 26–55 years, mean 40.7 years) had subnormal amplitudes at all luminances, but normal implicit times, and six (age 38–81 years, mean 60.7 years) had abnormal ERGs with marked reduction of a- and b-waves, and delayed implicit times of the b-wave. The implicit times of the a-wave were normal in all subjects. A reduction in the b/a wave ratios was not found, nor was there selective loss of scotopic, mixed rod/cone, or cone responses. The light/dark ratio of the EOG was subnormal (150–185%) or abnormal (below 150%) in all but three subjects. Two patients with normal EOG showed normal ERGs in both eyes, but one had subnormal ERGs in both eyes. The scotopic sensitivity was normal in all subjects and dark adaptation showed a normal time course. Colour vision was normal in all patients. CONCLUSION: The results suggest that in most cases the function of the retinal pigment epithelium is affected by this disease before any changes in the function of the sensory retina are detectable by our methods, and that retinal dysfunction is focal rather than diffuse.